(3QSGdI JfGhd CbOGM GdMb GdUQGM hTQH YPH RdGdg aj eYfi bhd GdeUdi Udi GdfHi hBdg YOO ceGd Gddg hceG jdjb HceGdgs - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eUWai GdcSjQ HdZg Gddg SGFQ CeGdg HLGg SjOfG eMeO Udi Gddg Ydjg hSde hef Qhi UMjM CbhGdg s
(3BNQgG (B:s
(3hCf jef YdjfG HGdNdGU ef TQhQ CfaSfG GdCeGQI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO GdCejf hYdi Bdg hUMHg CLejYf Bejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha (B208) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs